Engineering composites properties & applications - Mohd. Sapuan Salit (Universiti Putra Malaysia Press, 2014)
This book is focusing on the properties, characterization, design, fabrication and application of engineering composites. This book is equally beneficial for the readers from research and academic communities and for general readership